Implementasi dan Tantangan Regulasi Perlindungan Data Pribadi Pasien di Era Digital pada Rumah Sakit - Yudha Aditya Pradana (Jurnal Hukum Lex Generalis, 2024)
The development of information technology in the health sector has triggered the need for a strong and integrated patient personal data protection system. In the midst of the digital transformation of hospitals, the vulnerability to data leaks is increasing. The problem faced is how positive legal provisions in Indonesia regulate the protection of patient personal data in hospitals in the context of digital transformation and what challenges hospitals face in implementing regulations on patient personal data protection, and what efforts can be made to overcome them in the digital era. The research method used is normative juridical legal research. The results of the study show that positive legal provisions in Indonesia that regulate the protection of patient personal data include Law No. 27 of 2022 concerning Personal Data Protection which classifies health data as sensitive data, Law No. 36 of 2009 concerning Health which guarantees the confidentiality of medical information, and Permenkes No. 24 of 2022 concerning Medical Records which requires hospitals to maintain data security, both manual and digital. These provisions are the legal basis in the era of digital transformation of health services. The main challenges for hospitals are minimal infrastructure, low understanding of human resources, cyber threats, and overlapping regulations. Solution efforts: technology improvement, HR training, appointment of DPO, and preparation of SOPs and routine audits.